Salvation as healing? : an analysis of Jesse Mugambi and Mercy Oduyoye’s soteriologies in the context of African prosperity gospels - Umaru, Kefas Kure (Stellenbosch : Stellenbosch University, 2017)
Thesis (MTh)--Stellenbosch University, 2017.